2017
DOI: 10.3390/s17102220
|View full text |Cite
|
Sign up to set email alerts
|

Ag-Modified In2O3 Nanoparticles for Highly Sensitive and Selective Ethanol Alarming

Abstract: Pure In2O3 nanoparticles are prepared by a facile precipitation method and are further modified by Ag. The synthesized samples are characterized by scanning electron microscopy, transmission electron microscopy, energy dispersive X-ray spectroscopy, X-ray diffraction, Raman and UV-Vis spectra. The results show the successful heterojunction formation between Ag and In2O3. Gas sensing property measurements show that the 5 mol % Ag-modified In2O3 sensor has the response of 67 to 50 ppm ethanol, and fast response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Ag, another noble metal, has been used in low-cost material sensors. [168][169][170] Wang et al 168 reported a 3D hierarchical structure made from In 2 O 3 and subsequent Ag functionalization using a NaBH 4 reducing agent to construct 6 wt%-Ag-loaded In 2 O 3 nanoflower composite materials for HCHO sensing. The sensor exhibited enhanced sensitivity (R a /R g = 11.3) to 20 ppm gas, rapid response/recovery time (0.9 s/14 s), and high selectivity.…”
Section: Catalytic Functionalizationmentioning
confidence: 99%
“…Ag, another noble metal, has been used in low-cost material sensors. [168][169][170] Wang et al 168 reported a 3D hierarchical structure made from In 2 O 3 and subsequent Ag functionalization using a NaBH 4 reducing agent to construct 6 wt%-Ag-loaded In 2 O 3 nanoflower composite materials for HCHO sensing. The sensor exhibited enhanced sensitivity (R a /R g = 11.3) to 20 ppm gas, rapid response/recovery time (0.9 s/14 s), and high selectivity.…”
Section: Catalytic Functionalizationmentioning
confidence: 99%
“…The enlarged HDRs in ethanol lead to further suppression of conduction channel for hole transportation. On the other hand, the catalytic activity of Ag NPs promotes the adsorption, dissociation, and reaction of O 2 and ethanol on the LDH surface via so-called 'spillover' and 'back spillover' effects [3], causing a more marked contraction of conduction channel compared with the case of pure MgAl-LDHs. Besides, direct interaction between Ag NPs and the adsorbed ethanol molecules may occur.…”
Section: Gas-sensing Properties and Mechanismmentioning
confidence: 99%
“…The large number of traffic accidents triggered by drunk driving, with serious casualties and property losses every year, further necessitates the development of high-performance ethanol sensors for the ultrasensitive, rapid detection of alcohol concentration in exhaled breath. At present, various metal oxide semiconductors such as V 2 O 5 [1], ZnO [2], and In 2 O 3 [3] are widely used for sensing ethanol gas. However, metal oxide-based sensors generally must operate at a temperature higher than 150 °C in order to obtain decent sensitivity and a fast response.…”
Section: Introductionmentioning
confidence: 99%
“…As the least expensive noble metal, silver is intensively studied as a catalytically active modifier for sensor materials based on binary semiconductor oxides [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], nanocomposites [ 29 , 30 ], as well as semiconductor materials with a perovskite structure [ 31 , 32 , 33 ]. It was shown that introducing silver makes semiconductor oxides more sensitive to hydrogen H 2 [ 9 , 11 ], carbon monoxide CO [ 17 , 28 , 32 ], hydrogen sulphide H 2 S [ 10 , 14 , 18 ], sulphur dioxide SO 2 [ 12 ], ozone O 3 [ 23 ] and nitrogen oxides NO x [ 19 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that introducing silver makes semiconductor oxides more sensitive to hydrogen H 2 [ 9 , 11 ], carbon monoxide CO [ 17 , 28 , 32 ], hydrogen sulphide H 2 S [ 10 , 14 , 18 ], sulphur dioxide SO 2 [ 12 ], ozone O 3 [ 23 ] and nitrogen oxides NO x [ 19 , 24 ]. Recently, silver has been actively explored as a modifier for gas sensors with a high sensitivity to volatile organic compounds (VOCs) [ 13 , 15 , 16 , 20 , 21 , 22 , 25 , 26 , 27 , 29 , 30 , 31 , 33 ].…”
Section: Introductionmentioning
confidence: 99%